Liraglutide Exerts Potential Anti-inflammatory Effect in Type 1 Diabetes by Inhibiting IFN-γ Production via Suppressing JAK-STAT Pathway - Zhao, Yunjuan; Xie, Yunliang; Li, Wangen (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Background: Type 1 diabetes is a T cell-mediated autoimmune disease. Interferon γ plays a critical role in the pathogenesis of type 1 diabetes. Signal transducer and activator of transcription transduces type I interferon cytokines in T cells, leading to Th1 cell differentiation and production of interferon γ. Recent studies suggest that liraglutide reduces the plasma concentration of C-reative protein in patients with type 1 diabetes and protects β cell function in the non-obese diabetic mouse. Objective: The study aimed to explore the effect of glucagon-like peptide-1 analogue on interferon γ production and the underlying signaling pathway in vitro. Methods: Jurkat E6-1 cells were intervened with different concentrations of glucose and liraglutide during different time periods. Protein was extracted from Jurkat E6-1 cells. The target proteins (total and activated Janus kinase 2, signal transducers and activators of transcription 4 and interferon γ) were detected by Western blot. Results: Glucose stimulates interferon γ expression and activates Janus kinase 2/signal transducers and activators of transcription 4 signaling pathway in Jurkat E6-1 cells in a concentration and timedependent manner. Under high glucose condition, liraglutide inhibits interferon γ expression and Janus kinase 2/signal transducers and activators of transcription 4 signaling pathway in Jurkat E6-1 cells in a concentration and time-dependent manner. The Janus kinase responsible for liraglutide-inhibited signal transducers and activators of transcription 4 phosphorylation is Janus kinase 2, which is also required for the interferon γ induction. Finally, we demonstrated that under high glucose condition, liraglutide inhibits interferon γ expression via Janus kinase 2/signal transducers and activators of transcription 4 signaling pathway in Jurkat E6-1 cells. Conclusion: Liraglutide inhibits Jurkat E6-1 cells to produce interferon γ via the Janus kinase/signal transducers and activators of transcription signaling pathway under high glucose condition, which implies its potential in the immunoregulatory effect of type 1 diabetes.
Keywords: T cell